In grand style celebrations in Korean art during the Joseon dynasty - Han, Hyonjeong Kim (Asian Art Museum, 2013)
In Korea, life milestones have traditionally been celebrated with festivals and feasts. Such celebrations helped to define and honor an individual's identity. Based on a 2009 exhibition at the National Museum of Korea, the exhibition at the Asian Art Museum that this book documents incorporates new findings and researches. Co-organized by the Asian and the NMK, the show--which opens in San Francisco in October 2013--presents rare and exquisite objects drawn from some ten museums in Korea. Highlights include a ten-panel folding screen of Celebrations on the Crown Prince's Birth from 1874, a portrait of Emperor Gojong from 1897, a Royal Procession to the Royal Tomb at Hwaseong from 1795, and kings' thrones and palanquins. The book documents Korea's taste for splendor and grandeur. It explores the meaning and obligations of kingship, the elite culture of the court and the upper class during the Joseon dynasty (1392-1910), and the complex roles of women in organizing and presenting elaborate celebrations, in the grandest of styles.